Does the Unavailability of Educational Resources in Schools Determine Child Labor in Sub-Saharan Africa? A Micro-econometric Analysis from Cȏte d'Ivoire - Pokou Edouard Abou (International Journal of Economics & Management Sciences, 2016)
Child labor remains a concern for policy makers considering its interrelations with human capital formation. Indeed, in Sub-Saharan Africa and particularly in Cote d'Ivoire, children are still on the labor market. Several factors explain this fact of setting children to work. Given this diversity of determinants of child labor, this study aims to show the effects of school resources on child labor. Therefore, we use the 2010 national survey data on child labor and education policies. From a bivariate probit model, the results showed that the availability of certain school resources as a canteen and a drinking water point in the school promotes the education of children and especially girls. On the contrary, their unavailability forces parents to put their children on labor market. Therefore, one of the major policies to be implemented is to improve the learning environment of children by building school canteens and drinking water point in schools. It's a new challenge for policy makers to effectively fight against child labor and reach the goal of education for all and of quality in 2030.
Keywords: 330; Child labor; Educational resources; Bivariate probit; Micro-econometric; Poverty